Lineage-specific activities of a multipotent mitochondrion of trypanosomatid flagellates - Škodová-Sveráková, Ingrid; Verner, Zdeněk; Skalický, Tomáš; Votýpka, Jan; Horváth, Anton; Lukeš, Julius (Molecular microbiology, 2015)
Trypanosomatids are a very diverse group composed of monoxenous and dixenous parasites belonging to the excavate class Kinetoplastea. Here we studied the respiration of five monoxenous species (Blechomonas ayalai, Herpetomonas muscarum, H. samuelpessoai, Leptomonas pyrrhocoris and Sergeia podlipaevi) introduced into culture, each representing a novel yet globally distributed and/or species-rich clade, and compare them with well-studied flagellates Trypanosoma brucei, Phytomonas serpens, Crithidia fasciculata and Leishmania tarentolae. Differences in structure and activities of respiratory chain complexes, respiration and other biochemical parameters recorded under laboratory conditions reveal their substantial diversity, likely a reflection of different host environments. Phylogenetic relationships of the analysed trypanosomatids do not correlate with their biochemical parameters, with the differences within clades by far exceeding those among clades. As the S. podlipaevi canonical respiratory chain complexes have very low activities, we believe that its mitochondrion is utilised for purposes other than oxidative phosphorylation. Hence, the single reticulated mitochondrion of diverse trypanosomatids seems to retain multipotency, with the capacity to activate its individual components based on the host environment.
Keywords: Mitochondria; transport elektronů; Leishmania; Oxidative Phosphorylation; mitochondrie; oxidativní fosforylace; Electron Transport; Phylogeny; fylogeneze; Trypanosoma brucei brucei; Trypanosomatina